2004
DOI: 10.1029/2003jc002094
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent energy production and entrainment at a highly stratified estuarine front

Abstract: [1] Rates of turbulent kinetic energy (TKE) production and buoyancy flux in the region immediately seaward ($1 km) of a highly stratified estuarine front at the mouth of the Fraser River (British Columbia, Canada) are calculated using a control volume approach. The calculations are based on field data obtained from shipboard instrumentation, specifically velocity data from a ship mounted acoustic Doppler current profiler (ADCP), and salinity data from a towed conductivity-temperature-depth (CTD) unit. The resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
164
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 113 publications
(196 citation statements)
references
References 43 publications
(72 reference statements)
28
164
4
Order By: Relevance
“…Observations of river plumes have found that lift-off typically occurs uniformly across the cross section [e.g., Wright and Coleman, 1971], consistent with two-layer hydraulic theory [i.e., Armi and Farmer, 1986;Farmer and Armi, 1986], or at an angle to the cross section, consistent with a two-dimensional (2-D) extension of hydraulic theory [MacDonald and Geyer, 2005]. Landward of the lift-off location, the discharging water mass is essentially unmodified, but substantial mixing occurs seaward of the lift-off in both the Mississippi [Wright and Coleman, 1971] and Fraser River [MacDonald and Geyer, 2004] outflows.…”
Section: Plume Structurementioning
confidence: 81%
See 4 more Smart Citations
“…Observations of river plumes have found that lift-off typically occurs uniformly across the cross section [e.g., Wright and Coleman, 1971], consistent with two-layer hydraulic theory [i.e., Armi and Farmer, 1986;Farmer and Armi, 1986], or at an angle to the cross section, consistent with a two-dimensional (2-D) extension of hydraulic theory [MacDonald and Geyer, 2005]. Landward of the lift-off location, the discharging water mass is essentially unmodified, but substantial mixing occurs seaward of the lift-off in both the Mississippi [Wright and Coleman, 1971] and Fraser River [MacDonald and Geyer, 2004] outflows.…”
Section: Plume Structurementioning
confidence: 81%
“…The generic structure described here is likely to be consistent for a wide variety of plumes, from small scale industrial discharge plumes and tidal creeks to larger scale river plumes, particularly those that enter the ocean at supercritical speeds, such as the Mississippi [Wright and Coleman, 1971] or the Fraser [MacDonald and Geyer, 2004] Rivers. However, it is also likely that certain physical mechanisms may be more dominant at different scales, as discussed further in section 5.5.…”
Section: Conceptual View Of Plume Structure and Evolutionmentioning
confidence: 99%
See 3 more Smart Citations